2014
DOI: 10.1186/1476-9255-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Salivary histatin 3 inhibits heat shock cognate protein 70-mediated inflammatory cytokine production through toll-like receptors in human gingival fibroblasts

Abstract: BackgroundSalivary histatins are bioactive peptides related to the innate immune system associated with antimicrobial activities. However, very little is known about the physiological and biological functions of histatins against host cells or their role in oral cell inflammation. Histatin 3 binds to heat shock cognate protein 70 (HSC70, a constitutively expressed heat shock protein (HSP)). It is unclear whether HSC70 is involved in the inflammatory response in oral cells. Injured oral cells release some intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…31 This was accompanied by evidence of impaired innate local defenses with reduced histatins 1 and 5 and lysozyme. 32 This extends a study of increased fecal secretory IgA into saliva in cirrhosis and points to an overall activation of systemic inflammation, potentially through contributors in the gut and oral cavity. 33 Interestingly, whereas there clearly were differences in systemic inflammatory response in previous HE, compared to no-HE, we did not find similar changes in salivary inflammatory response between these subgroups.…”
Section: Discussionsupporting
confidence: 68%
“…31 This was accompanied by evidence of impaired innate local defenses with reduced histatins 1 and 5 and lysozyme. 32 This extends a study of increased fecal secretory IgA into saliva in cirrhosis and points to an overall activation of systemic inflammation, potentially through contributors in the gut and oral cavity. 33 Interestingly, whereas there clearly were differences in systemic inflammatory response in previous HE, compared to no-HE, we did not find similar changes in salivary inflammatory response between these subgroups.…”
Section: Discussionsupporting
confidence: 68%
“…The levels of collagen type I in the media were measured using the biotinylated anti-collagen type I antibody (0.2 g/ml). The ELISA procedure was performed as described in the user manual of the CytoSet kits (Biosource) 23) .…”
Section: Enzyme-linked Immunosorbent Assays (Elisas)mentioning
confidence: 99%
“…TLR2 has been identified to activate cells in response to heat-shock protein 70 [33] and necrotic cells [32,34]. Recent reports have shown that HSC70 released from the damaged cells may stimulate human gingival fibroblasts (HGFs) [35,36]. Considering this information, our data suggest that DAMPs can directly activate gingival fibroblast via TLR-2 and regulated cell activation.…”
Section: Discussionmentioning
confidence: 60%